2017
DOI: 10.18103/imr.v3i5.443
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets, potential biomarker and metabolic target in glioblastoma

Abstract: Lipid droplets (LDs) are subcellular organelles that store large amounts of the neutral lipids, triglycerides (TG) and/or cholesteryl esters (CE). LDs are commonly formed in adipocytes, liver cells and macrophages, and their formation has been shown to be associated with the progression of metabolic diseases, i.e., obesity, fatty liver and atherosclerosis. Interestingly, LDs are also found in some tumor tissues. We recently showed that LDs are prevalent in glioblastoma (GBM), the most deadly brain tumor, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 93 publications
3
35
0
Order By: Relevance
“…Evidently, three of the remaining four essential genes have a clear role in lipid metabolism, e.g., cardiolipin synthesis and carnitine transport. Elevated lipid levels and reprogramming of lipid metabolism have previously been reported for GBM and findings related to lipid metabolism are therefore to be expected (Geng and Guo, 2017). One of the three genes is SLC22A5, a membrane protein responsible for the cellular uptake of carnitine (UniProt Consortium, 2018).…”
Section: Validation and Function Of The Found Essential Genesmentioning
confidence: 99%
“…Evidently, three of the remaining four essential genes have a clear role in lipid metabolism, e.g., cardiolipin synthesis and carnitine transport. Elevated lipid levels and reprogramming of lipid metabolism have previously been reported for GBM and findings related to lipid metabolism are therefore to be expected (Geng and Guo, 2017). One of the three genes is SLC22A5, a membrane protein responsible for the cellular uptake of carnitine (UniProt Consortium, 2018).…”
Section: Validation and Function Of The Found Essential Genesmentioning
confidence: 99%
“…LDs itself have been proposed as novel diagnostic biomarkers for glioblastoma. It has been demonstrated that while they are not detectable in low-grade gliomas or normal brain tissues, they are common in glioblastoma, the most lethal brain tumor (70). Among the LD-associated proteins, there are enzymes of the sterol biosynthetic pathway, the acyl-CoA metabolism (ACSLs), and triacylglycerol (TAG) biosynthesis.…”
Section: Regulation Of Fa Storage and Intracellular Fa Mobilization (mentioning
confidence: 99%
“…Excessive lipids and cholesterol in cancer cells are converted to triglycerides and cholesteryl esters (CE) for storage in lipid droplets (LDs). Several reports indicate increased amount of lipid droplets in various types of tumors including leukemia, glioblastoma, renal clear cell carcinoma, and cancers of the prostate, colon, breast and pancreas [10][11][12][13][14][15][16]. As observed in these cancers, CE were shown to be the major component of LDs within cancerous tissue as compared to normal tissue [17].…”
Section: Introductionmentioning
confidence: 89%
“…Whereas ACAT-2 is associated with lipoprotein particle secretion, ACAT-1 is ubiquitous and known to maintain cellular cholesterol homeostasis. ACAT-1 mediated accumulation of CE was shown to positively correlate with poor survival in pancreatic and prostate cancers [12,13,[22][23][24][25][26][27]. While the role of ACAT-1/CE accumulation is being studied in various cancers, information regarding the contribution of these mediators in ovarian cancer is relatively scarce.…”
Section: Introductionmentioning
confidence: 99%